PREVENTION OF SEPSIS IN CRITICAL ENVIRONMENTS TO HEALTH: CARE STRATEGIES - Estefani Silva Nascimento, Thalita; Tavares Fialho Bezerra, Sayonara; Paula dos Santos Nascimento, Jerssycca; Paula do Nascimento, Raybarbara; Kelly Araújo Silva Melo, Geni; Conceição de Assis, Jefferson; Carolinne Marie dos Santos Gomes, Anne; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
The first step to prevent SEPSE is to follow the vaccination schedule for children and adults is to avoid the exaggerated use of antibiotics and self-medication, not forgetting proper hand hygiene. Sepsis can develop through exposure to etiological agents present in the environment in which the individual lives on a daily basis, which settle down and trigger a reaction in the body, according to the person’s physiological particularities. ANVISA (National Health Surveillance Agency) has created programs for the implementation, monitoring and provision of technical materials so that HAIs are reduced at all levels of assistance in the health network.